Spatio-temporal distribution characteristics and influencing factors of drought in the Liaohe river basin, China - Gong, Yuanshan (Frontiers in Environmental Science, 2022)
Effective identification of drought-related events and quantitative analysis of the spatio-temporal evolution of drought are essential for regional disaster prevention and mitigation and sustainable development. Based on monthly precipitation and average temperature data from 113 grid points in the Liaohe River Basin (LRB) from 1961 to 2018, this study evaluated the standardized precipitation evapotranspiration index (SPEI) on monthly, quarterly, 6-monthly, and annual scales. Run-length theory was used to extract three characteristic variables of drought—frequency, severity, and duration—for different grades of drought. Linear regressions, Manner–Kendall mutation tests, correlations, and other methods were used to analyze the spatio-temporal distribution characteristics of the different levels of drought and their influencing factors. Results from this research can provide a scientific reference for disaster prevention and mitigation, water conservancy project planning and construction, land space ecological restoration, and development and protection in the LRB. Our results indicated the following: (i) overall, from 1961 to 2018, the short-term SPEI (monthly, quarterly) showed an upward trend (0.06/103a, 0.01/103a), while the long-term SPEI (6-monthly, annual) showed a downward trend (-0.01/103a, -0.3/103a), and the overall change occurred in three stages, specifically stable–decline–increase. From a seasonal point of view, the SPEI in spring, summer, and autumn showed an upward trend, and although the SPEI showed multiple mutations during all seasons, they were not significant (P > 0.05). (ii) Moderate drought occurred the most frequently (32 times) and was concentrated in the northern and western parts of the LRB. The severity of extreme drought in the upper reaches of the Chagan Mulun River was low, with a minimum SPEI of -7.07, and the durations of mild, moderate, severe, and extreme drought were 2, 2–2.5, 2–3, and 3–4 months, respectively. (iii) SPEI-1 (monthly) showed the strongest correlation with precipitation and air temperature, which decreased with increasing time frames, such that SPEI-12 (annual) showed the weakest correlation. The correlations between SPEI and precipitation at different time scales were all highly significant (P < 0.01), and the correlation strength was much greater than that for air temperature, indicating that precipitation had the most significant impact on drought conditions in the LRB.